2015
DOI: 10.1001/jamasurg.2014.3867
|View full text |Cite
|
Sign up to set email alerts
|

Role of Repeat18F-Fluorodeoxyglucose Positron Emission Tomography Examination in Predicting Pathologic Response Following Neoadjuvant Chemoradiotherapy for Esophageal Adenocarcinoma

Abstract: To our knowledge, this is the largest study examining the role of PET CT characteristics in esophageal adenocarcinoma for patients undergoing neoadjuvant chemoradiotherapy that demonstrates that δ SUV of less than 45% is associated with patients with residual disease but not CPR. Based on the findings from our study, the current recommendation is still surgical resection regardless of the posttherapy PET SUV in the primary tumor. However, our study highlights the ability to detect patients with residual diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 30 publications
0
35
1
Order By: Relevance
“…Twenty-eight publications were left after checking the full texts. Six studies were out for not enough information to construct 2 × 2 contingency table (11)(12)(13)(14)(15)(16). For that the main purpose of the present study is to evaluate the therapeutic response of the primary tumor to NCRT, six studies in which pathological response criteria were consisted of lymph nodes or metastatic diseases regression assessment were excluded (17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight publications were left after checking the full texts. Six studies were out for not enough information to construct 2 × 2 contingency table (11)(12)(13)(14)(15)(16). For that the main purpose of the present study is to evaluate the therapeutic response of the primary tumor to NCRT, six studies in which pathological response criteria were consisted of lymph nodes or metastatic diseases regression assessment were excluded (17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…These findings could reflect that NT was in more advanced status. Also, the survival superiority of NT followed by surgery over prompt surgery could result from occult metastases undetected by PET-CT (11,15). We also attribute this finding to the survival superiority of NT followed by surgery over prompt surgery.…”
Section: Discussionmentioning
confidence: 79%
“…No definitive findings or established guidelines have been published for the evaluation of esophageal tumors (tumor) and regional LN using PET-CT in patients with esophageal cancer (2,7,8,10). In addition, it remains unclear whether PET-CT findings vary between patients treated with and without NT (2,11). The purpose of the present study is to clarify any variation in PET-CT findings between esophageal cancer patients treated with and without NT and to predict LN metastases for better prognosis.…”
Section: Introductionmentioning
confidence: 93%
“…Kukar et al reported in 77 patients and noted that less than 45% SUV decrease was a risk factor for residual disease (25). Another study with 53 EAC patients reported that a decrease of >23.5% SUV resulted in the sensitivity and specificity for (21,23,28).…”
Section: Predicting Preoperative Chemoradiation Response By Pet-ctmentioning
confidence: 98%